The Role of Sports Teachers and Parents in Adaptive Physical Education Learning in Children with Special Needs: Case Study - Raga Kusuma Atmaja; Nurhidayat (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine how big the teacher's role is in the development of adaptive physical education in children with special needs. This research was conducted at SLB D/D1 YPAC Surakarta. The population and sample in this study were two sports teachers and three parents of children with special needs. Questionnaires and interviews are the sampling techniques in this study. This study uses a quantitative descriptive method. The technical steps of data analysis in this study include data reduction, data verification, and conclusion. The results of this study are that sports teachers play a bigger role than parents of children with special needs. The percentage of the role of sports teachers is 55% while the parents of students are 45%. Aspects of learning methods carried out by teachers and parents belong to a good category. Meanwhile, the aspect of learning modification carried out by sports teachers is more creative and innovative because it uses tools that can support the achievement of learning objectives. Moral support provided by sports teachers at schools to children with special needs is one of the things that children with special needs need in carrying out adaptive physical learning. In addition, the role of sports teachers in guiding and supporting children with special needs has a wider relationship than parents. Moral support provided by sports teachers at schools to children with special needs is one of the things that children with special needs need in carrying out adaptive physical learning. In addition, the role of sports teachers in guiding and supporting children with special needs has a wider relationship than parents. Moral support provided by sports teachers at schools to children with special needs is one of the things that children with special needs need in carrying out adaptive physical learning. In addition, the role of sports teachers in guiding and supporting children with special needs has a wider relationship than parents.